Pengaruh Alelokimia Ekstrak Ubi Talas (Collocasia esculenta) dan Umbi Gadung (Discorea hispida dennst.) terhadap Perkecambahan Gulma Asystasia gangetica - Pujisiswanto, Hidayat; Susanto, Herry; Sriyani, Nanik; Putri, Alda Anisya; Anggraini, Fenny Dwi (JURNAL AGROTROPIKA, 2022)
The presence of Asystasia gangetica weed in oil palm plantations is detrimental and need to be controlled. One alternative to control weeds is by utilizing allelochemical compounds as bioherbicides. This study aimed to determine the allelochemical effect of taro tubers (Colocasia esculenta L.) and gadung tubers (Dioscorea hispida) extracts on the germination of A. gangetica weeds. The research was carried out at the Weed Science Laboratory, Faculty of Agriculture, University of Lampung from November to December 2021. The research design used a Completely Randomized Design (CRD) with 2 factors, the first factor was the concentration of the extract: 0% (Control), 10%, 20% and 30%. The second factor was the source of the extract: taro tubers and gadung tubers. The homogeneity test of variance is using the Bartlett test. If the assumptions are met, the data analysis is continued with the variance test and the Least Significant Difference (BNT) test at the 5% level. The results showed that extracts of taro and gadung tubers at 10%, 20%, and 30% concentrations were able to inhibit germination and reduce the speed of germination of A. gangetica weeds. The inhibitory power of gadung tubers and taro tubers extracts at 20% and 30% concentrations were able to inhibit germination and the speed of germination up to 100%. The inhibition of taro tuber extract was higher than gadung tuber on germination rate of A. gangetica weed. Key words: Asystasia gangetica, allelopathy, germination, taro, yam